Neurochemical phenotype and function of endomorphin 2-immunopositive neurons in the myenteric plexus of the rat colon - Li, Yun-Qing (Frontiers in Neuroanatomy, 2014)
The distribution and activity of endomorphins (EMs), which are endogenous m-opioid receptor (MOR) ligands in the gastrointestinal tract (GI), have yet to be elucidated. The current study aimed to shed light on this topic. EM2 was expressed in the enteric neurons in the myenteric plexus of the mid-colon. Of the EM2-immunoreactive (EM2-IR) neurons, 53 ± 4.6%, 26 ± 4.5%, 26 ± 2.8% and 49 ± 4.2% displayed immunopositive staining for choline acetyl transferase (ChAT), substance P (SP), vasoactive intestinal peptide (VIP) and nitric oxide synthetase (NOS), respectively. A bath application of EM2 (2 mM) enhanced spontaneous contractile amplitude and tension, which were reversed by β-FNA (an antagonist of MOR) but not NG-nitro-L-arginine methyl ether (L-NAME, a non-selective inhibitor of NOS) or vasoactive intestinal peptide (VIP)6-28 (an antagonist of the VIP receptor) in the colonic strips. EM2 significantly suppressed inhibitory junction potentials (IJPs) in 14 of the 17 examined circular muscle cells, and this effect was not antagonized by preincubation in L-NAME. EM2 was widely expressed in interneurons and motor neurons in the myenteric plexus and presynaptically inhibited fast IJPs, thereby enhancing spontaneous contraction and tension in the colonic smooth muscle.